Efficacy of CO2-baited mosquito catchers in controlling vector mosquitoes in residential areas of China - Wu, Yuyan; Zhang, Chuan; Peng, Yanyang; Sun, Jimin; Gong, Zhenyu; Ling, Feng (Frontiers in Veterinary Science, 2025)
IntroductionVector-borne diseases significantly impact global health. Mosquitoes are key vectors for transmitting such diseases, making mosquito control crucial for disease prevention. Carbon dioxide is commonly used in surveillance traps to attract mosquitoes. However, its application in mosquito abatement devices is limited due to environmental and logistical constraints related to continuous CO2 emissions. In China, a new mosquito trap utilizing CO2 was developed using nanoporous silicon-based polymer materials to capture and release CO2 from the air. This study aimed to assess the operational efficiency of this CO2-enhanced trap in reducing mosquito populations and its potential for residential vector control applications.MethodsTwo residential villages with similar mosquito densities and geographic environments were selected for field trials in Ningbo City in 2024. One village was randomly assigned as the control group, while the other served as the test group. Within the test group, three zones were artificially divided to evaluate the effect and scope of the breath-activated mosquito trap in managing mosquito populations. Adult and larval mosquito densities were monitored bi-monthly before and after the trials using BG traps, CDC light traps, and the larval pipette method.ResultsLarval and adult mosquito densities were monitored for four months before the trials to establish the baseline mosquito density between the test and control villages; no statistical differences were found (larval, U = 35, p = 0.798 > 0.05; adults, CDC light trap U = 41, p = 0.442 > 0.05, BG trap U = 43, p = 0.279 > 0.05). After the trials began, standard decreasing rates of larval and adult mosquito densities were observed, with 36.24%–46.93% larval mosquito density decreasing, 38.22%–65.91% (CDC light traps), and 43.05%–73.30%; BG traps. Statistically significant differences were found between Zone I and the control village for larval and adult mosquitoes (GLMM, larval p = 0.026; adult CDC light trap p = 0.009; BG trap p = 0.027).DiscussionBreathing catchers using CO2 can effectively control larval and adult mosquito densities in a range of regions. Without insecticide usage and excess CO2 emissions, this might be an effective choice for mosquito control in residential areas to prevent mosquito-borne diseases.